Analysis of the Toll-Like Receptor 2-2 (TLR2-2) and TLR4 mRNA Expression in the Intestinal Mucosal Immunity of Broilers Fed on Diets Supplemented with Nickel Chloride - Bangyuan Wu (International Journal of Environmental Research and Public Health, 2014)
Toll-like receptor (TLRs) are important innate immune receptors, and TLR2 and TLR4 play an important role in intestinal mucosal innate immunity. It has been found that nickel (Ni) can affect the immune system in broilers. The purpose of this study was to analyze changes in TLR2-2 and TLR4 mRNA expression levels in the intestinal mucosal immunity system of broilers induced by dietary nickel chloride (NiCl2) using quantitative real-time polymerase chain reaction (qRT-PCR) assays. Two hundred and forty one-day-old avian broilers were divided into four groups and fed on a corn-soybean basal diet as control diet or the same basal diet supplemented with 300, 600 and 900 mg/kg of NiCl2 for 42 days. Results showed that the TLR2-2 and TLR4 mRNA expression levels in the intestinal mucosa and the cecal tonsil were lower (p < 0.05 or p < 0.01) in the 300, 600 and 900 mg/kg groups than those in the control group. It was concluded that dietary NiCl2 in excess of 300 mg/kg could reduce TLR2-2 and TLR4 mRNA expression levels in the intestinal mucosa and cecal tonsil in broilers, implying that the innate immunity in intestinal mucosal immune system could be impaired by pathways involving injured surface epithelium cells or/and the inhibition of the TLR signal transduction.